2004
DOI: 10.1016/j.mrfmmm.2004.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome analysis of mouse one-cell androgenones derived from a sperm nucleus exposed to topoisomerase II inhibitors at pre- and post-fertilization stages

Abstract: Mouse spermatozoa and androgenetic one-cell embryos (androgenones) at various developmental stages were exposed to etoposide (1 µM), a topoisomerase II (topo II) poison, or to either of two catalytic inhibitors:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Previous research has reported that spermatozoal chromosomal damage occurs in some extreme environments (Tateno et al 2000, Tateno & Kamiguchi 2004. Furthermore, in our study, fewer embryos that had been injected with NaOH-treated spermatozoa reached the M/B stage than did those injected with fresh spermatozoa.…”
Section: Influence Of Naoh Treatment Of Spermatozoa Dnasupporting
confidence: 38%
“…Previous research has reported that spermatozoal chromosomal damage occurs in some extreme environments (Tateno et al 2000, Tateno & Kamiguchi 2004. Furthermore, in our study, fewer embryos that had been injected with NaOH-treated spermatozoa reached the M/B stage than did those injected with fresh spermatozoa.…”
Section: Influence Of Naoh Treatment Of Spermatozoa Dnasupporting
confidence: 38%
“…In addition, mouse acrosome enzymes can potentially induce deformation and degeneration of oocytes [30], and the removal of sperm plasma membrane and acrosome before ICSI improves embryonic development in mice [31]. Because inhibition of topological rearrangement of DNA during sperm chromatin remodeling causes DNA lesions [32,33], it is highly possible that the alteration of sperm chromatin remodeling by the acrosomal plasma membrane cholesterol and/or the acrosome can lead to structural chromosome aberrations of paternal origin. TYH is widely used for mouse IVF program because it can effectively promote sperm capacitation and trigger the acrosome reaction [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggest a role for Top2 after fertilization during sperm decondensation and pronuclear formation. However, it is not clear whether this activity in the oocyte is due to paternally or maternally derived enzyme (Bizzaro et al 2000, St Pierre et al 2002, Tateno & Kamiguchi 2004). Regardless, inheritance of an intact sperm nuclear matrix, regulated by Top2, is expected to be essential to the initial stages of development as it likely orders the paternal chromatin structure.…”
Section: The Sperm Nuclear Matrixmentioning
confidence: 99%